Hard Carbon Derived from Avocado Peels as a High-Capacity, Fast Na+ Diffusion Anode Material for Sodium-Ion Batteries. (29th August 2022) - Genier, Francielli Silva; Pathreeker, Shreyas; Schuarca, Robson Luis; Islam, Mohammad; Hosein, Ian Dean
Abstract : Deriving battery grade materials from natural sources is a key element to establishing sustainable energy storage technologies. In this work, we present the use of avocado peels as a sustainable source for conversion into hard carbon-based anodes for sodium ion batteries. The avocado peels are simply washed and dried then proceeded to a high temperature conversion step. Materials characterization reveals conversion of the avocado peels in high purity, highly porous hard carbon powders. When prepared as anode materials they show to the capability to reversibly store and release sodium ions. The hard carbon-based electrodes exhibit excellent cycling performance, namely, a reversible capacity of 352.55 mAh g −1 at 0.05 A g −1, rate capability up to 86 mAh g −1 at 3500 mA g −1, capacity retention of >90%, and 99.9% coulombic efficiencies after 500 cycles. Cyclic voltammetry studies indicated that the storage process was diffusion-limited, with diffusion coefficient of 8.62 × 10 −8 cm 2 s −1 . This study demonstrates avocado derived hard carbon as a sustainable source that can provide excellent electrochemical and battery performance as anodes in sodium ion batteries.